The effect of perceptual reasoning abilities on confrontation naming performance: An examination of three naming tests. Issue 3 (15th March 2016) - Soble, Jason R.; Marceaux, Janice C.; Galindo, Juliette; Sordahl, Jeffrey A.; Highsmith, Jonathan M.; O'Rourke, Justin J. F.; González, David Andrés; Critchfield, Edan A.; McCoy, Karin J. M.
ABSTRACT: Introduction : Confrontation naming tests are a common neuropsychological method of assessing language and a critical diagnostic tool in identifying certain neurodegenerative diseases; however, there is limited literature examining the visual–perceptual demands of these tasks. This study investigated the effect of perceptual reasoning abilities on three confrontation naming tests, the Boston Naming Test (BNT), Neuropsychological Assessment Battery (NAB) Naming Test, and Visual Naming Test (VNT) to elucidate the diverse cognitive functions underlying these tasks to assist with test selection procedures and increase diagnostic accuracy. Method : A mixed clinical sample of 121 veterans were administered the BNT, NAB, VNT, and Wechsler Adult Intelligence Scale–4th Edition (WAIS–IV) Verbal Comprehension Index (VCI) and Perceptual Reasoning Index (PRI) as part of a comprehensive neuropsychological evaluation. Results : Multiple regression indicated that PRI accounted for 23%, 13%, and 15% of the variance in BNT, VNT, and NAB scores, respectively, but dropped out as a significant predictor once VCI was added. Follow-up bootstrap mediation analyses revealed that PRI had a significant indirect effect on naming performance after controlling education, primary language, and severity of cognitive impairment, as well as the mediating effect of general verbal abilities for the BNT ( B = 0.13; 95% confidence interval, CI [.07, .20]), VNT ( B = 0.01; 95% CI [.002, .03]), and NAB ( B = 0.03; 95% CI [.01, .06]). Conclusions : Findings revealed a complex relationship between perceptual reasoning abilities and confrontation naming that is mediated by general verbal abilities. However, when verbal abilities were statistically controlled, perceptual reasoning abilities were found to have a significant indirect effect on performance across all three confrontation naming measures with the largest effect noted with the BNT relative to the VNT and NAB Naming Test.